Policy Review on Teachers’ Professional Development Framework 2072: An Anthropological Approach - Acharya, Milan (Education and Development, 2024)
Using an anthropological approach, this study examines how Teacher Professional Development (TPD) policies are implemented in public schools in Nepal. In so doing, the differences between the goals of the policies and their actual execution have been analyzed. The study focuses on the analysis of how TPD policy is applied at public high school levels. It emphasizes the need for targeted interventions to close the implementation gap between policy objectives and goals, promoting a positive school environment for teachers' professional development. A qualitative research design is used to administer in-depth interviews with four high school teachers. Conversational and thematic analyses are used to draw on the qualitative information. It is found found that the teachers have faced obstacles throughout TPD framework implementation. It is also found that institutional constraints, cultural norms, and resource limits have created a gap between policy objectives and on-the-ground realities. The teachers recognize the value of TPD policies in directing professional development and enhancing students learning, despite the challenges. Furthermore, observations from the teachers indicate the need to highlight the vital role that TPD plays in supplying teachers with cutting-edge teaching strategies and encouraging continuous professional development. The study details the value of culturally aware and contextually appropriate TPD tactics in improving student learning outcomes and encouraging teachers to embrace lifelong learning.